PROTEIN DENSITY AND QUALITY OF KORO KRATOK (Phaseolus lunatus L. Sweet ) AND KACANG TUNGGAK (Vigna unguiculata L. Walp) - Tejasari Tejasari (UPT Penerbitan Universitas Jember)
Proteins are macronutrient, plays important roles inhuman health. It is essential to life because it is avital par of the nucleus and protoplasm of every cell.The outer layers of skin, the hair, and the nailsconsist of almost entirely of an insoluble proteincalled keratin. The most active and abundant tissuesof the body – the muscles and glandular organs- arehigh in protein content. Lean muscles, heart, andliver contain 17-21 percent protein. Connectivetissues consists mainly of protein. Blood carries theimportant iron-containing protein hemoglobin in redblood cells. Therefore, the 50 gram dailyrequirement is a must to be fulfilled.Protein are larger and more complex moleculesthan those of either fats or carbohydrate. The largemolecules of protein made up of great number ofamino acids. The number of difference amino acidsin the molecules of certain protein varies from 8 to18 according to the size and complexity of themolecules of different protein. The number andcomposition of essential amino acids of proteindetermine utility of the protein for human health.Human obtain proteins from animal and plant foodsources. Nuts food group is plant origin of foodprotein since it contain high protein, range from 17-30 percent. Koro kratok (Phaseolus lunatus L. Sweet)and kacang tunggak ( Vigna unguiculata (L.) Walp)(Kasno and Achmad, 1988) are kinds of nut thathave high protein content. However, its highamount of protein does not explain utilizing of thenut protein for human health. Intake of 50 gramprotein does not explain the quality of protein.Therefore, it is important to evaluate the quality nutprotein.